1976
DOI: 10.1029/rs011i003p00179
|View full text |Cite
|
Sign up to set email alerts
|

Global features of lower ionospheric radio wave absorption in relation to middle atmospheric temperature variation and wind circulation

Abstract: The A1 absorption data for a large number of stations have been utilized to study the global features of the lower ionospheric radio wave absorption. The seasonal index ns (defined in the relation L = Bs (cos χ)ns, where L is the monthly median value of absorption, and χ, the midmonth solar zenith angle), is found to decrease rapidly and smoothly with increasing latitude and also with increasing solar activity for all stations. The constant cos χ plot of seasonal values of absorption versus month shows summer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Sechrist [1967] and Offermann [1977], however, have pointed out that temperature increases in the mesosphere are correlated well to this phenomenon. Samanta [1976] and Rees et al [1979] have reported that wind circulations and the associated temperature variations have a corre- far larger than the area estimated in the past by several au-The fmin data are also used for analysis assuming that fmin _ thors (-•1000 kmin diameter by Thomas[1961] and-2000 km enhancement (FME) is a reliable measure of occurrence of by Schwentek [1974]) and that the winter anomaly is closely absorption enhancement (see part l). The fmin data are taken correlated to occurrence of geomagnetic storm.…”
Section: Introductionmentioning
confidence: 99%
“…Sechrist [1967] and Offermann [1977], however, have pointed out that temperature increases in the mesosphere are correlated well to this phenomenon. Samanta [1976] and Rees et al [1979] have reported that wind circulations and the associated temperature variations have a corre- far larger than the area estimated in the past by several au-The fmin data are also used for analysis assuming that fmin _ thors (-•1000 kmin diameter by Thomas[1961] and-2000 km enhancement (FME) is a reliable measure of occurrence of by Schwentek [1974]) and that the winter anomaly is closely absorption enhancement (see part l). The fmin data are taken correlated to occurrence of geomagnetic storm.…”
Section: Introductionmentioning
confidence: 99%